2004
DOI: 10.1149/1.1803434
|View full text |Cite
|
Sign up to set email alerts
|

New Generation of Ordered Polymer Electrolytes for Lithium Batteries

Abstract: In poly͑ethylene oxide͒-based solid electrolytes, ionic conduction can occur by cations moving inside the helix ͑along the helix axis͒ and by anions moving on its envelope. This particular mode of ion transport can be enhanced by alignment of the polymeric structural units. We describe a procedure for orienting the helices in the perpendicular direction, the result of which is a oneorder-of-magnitude increase in polymer electrolyte ͑PE͒ conductivity and a similar decrease in PE/electrode interphase resistance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…The approach is well known since the first report by Scrosati and co‐workers [ 169 ] in 1998, lately intensively studied for application in polymeric lithium batteries. [ 170–174 ] The same group [ 167 ] investigated the effect of nanometric SiO 2 to a PEO/NaTFSI mixture. They demonstrated best performances with an EO/Na ratio of 20, and using the 5% wt SiO 2 , giving an ionic conductivity of 10 −5 S cm −1 and a Na transference number (t Na+ ) of 0.51.…”
Section: Electrolytes For Na‐based Rechargeable Batteriesmentioning
confidence: 99%
“…The approach is well known since the first report by Scrosati and co‐workers [ 169 ] in 1998, lately intensively studied for application in polymeric lithium batteries. [ 170–174 ] The same group [ 167 ] investigated the effect of nanometric SiO 2 to a PEO/NaTFSI mixture. They demonstrated best performances with an EO/Na ratio of 20, and using the 5% wt SiO 2 , giving an ionic conductivity of 10 −5 S cm −1 and a Na transference number (t Na+ ) of 0.51.…”
Section: Electrolytes For Na‐based Rechargeable Batteriesmentioning
confidence: 99%
“…[2][3][4] So far, the polymer electrolyte application in lithium cells has been hindered by several issues, such as the limited conductivity at the room temperature, the low stability of the Li-electrolyte interface, the low lithium transference number and the poor mechanical properties. A great enhancement of the PEO electrolyte characteristics in terms of stability against the lithium metal, Li-ion transport ability and mechanical properties, has been obtained by adding ceramic powders to the membrane, such as titanium oxide, TiO 2 [5][6][7][8][9][10], aluminum oxide, Al 2 O 3 [11][12][13][14][15][16], silicon oxide, SiO 2 [17][18][19][20], and zirconium oxide, ZrO 2 [21][22][23][24][25][26]. Indeed, it has been reported that the interactions between the metal oxide surface, the polymer and the lithium salt may efficiently improve the electrolyte characteristics [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, alignment of the polymer backbones and crystalline units by stretching [22][23][24] and by magnetic fields [25] have been found to increase ionic conduction by an increased factor of 4-40-fold. Dang et al [26] have seen anisotropic ionic conduction in rigidrod, liquid-crystalline polymers while Hubbard et al [27] aligned liquid-crystalline polymer electrolytes by use of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%